TATALAKSANA KESEHATAN LINGKUNGAN PUSKESMAS SUNGAI RAYA KABUPATEN INDRAGIRI HILIR - M.kamali Zaman (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2021)
Environmental health service efforts at the health center require comprehensive preparation of the personnel (executor) resource structure as well as financial resources - facilities and standard operating procedures. To clarify the scope of the implementation of Environmental Health Services in Public Health Center, it is necessary to regulate the description of Environmental Health Service activities as a reference for Public Health Center officers and communities who need these services. This study aims to determine the management of the Environmental Health Program at Sungai Raya Public Health Center. This type of research is qualitative with an analysis technique (in-depth analysis) by examining the components of environmental health services at public health centers. This research focuses on environmental health services, observed in the field by conducting in-depth interviews, observations, and reviewing documents. The informants in this study were selected based on the purposive sampling method (non-probability), which is in accordance with the principles of appropriateness and adequacy.